2020
DOI: 10.1057/s41304-020-00258-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving a self-assessment tool to monitor generic skills development in an active learning environment

Abstract: Improving a self-assessment tool to monitor generic skills development in an active learning environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Today society needs mobile teachers who continue to learn and improve their personal and professional qualities where teachers learn independently and self-assess because the knowledge and skills acquired at the university are insufficient to solve dynamic school problems (Pasternatskyi et al, 2022). The results of this study also confirmed that learning and self-assessment are transitions in education that cannot be avoided (Groen, Bijsmans, & Adriaensen, 2020). Currently, the application has not distinguished the aspects of self-efficacy and outcome expectancy due to limitations in calculating using certainty factors.…”
Section: Acceptedsupporting
confidence: 64%
“…Today society needs mobile teachers who continue to learn and improve their personal and professional qualities where teachers learn independently and self-assess because the knowledge and skills acquired at the university are insufficient to solve dynamic school problems (Pasternatskyi et al, 2022). The results of this study also confirmed that learning and self-assessment are transitions in education that cannot be avoided (Groen, Bijsmans, & Adriaensen, 2020). Currently, the application has not distinguished the aspects of self-efficacy and outcome expectancy due to limitations in calculating using certainty factors.…”
Section: Acceptedsupporting
confidence: 64%
“…We referred to the WHO guideline on translating and adapting an instrument. 16 The authors had acquired permission to use the instrument from Groen et al 1 Ethical clearance was obtained from the Research Ethics Committee at Atma Jaya Catholic University of Indonesia. The WHO process consists of five stages: 1) forward translation, 2)…”
Section: Methodsmentioning
confidence: 99%
“…The details of the component correlation matrix are presented in Table 2. This paper described the cross-cultural adaptation and psychometric testing process of the Indonesian version of Generic Skills Self-Assessment for Medical Students that was proposed by Groen et al 1 Initially, we meant to only translate the instrument into Bahasa Indonesia to keep the meaning of each item as close as possible to the original instrument as well as to simplify the process. Most of the changes we made during translation included simplifying the English terms and expressions.…”
Section: Internal Reliability and Construct Validitymentioning
confidence: 99%
See 2 more Smart Citations